Introducing communication theory analysis and application - West, Richard L.; Turner, Lynn H. (McGraw-Hill Education, 2018)
Introducing Communication Theory: Analysis and Application, focuses on the links between theory and everyday experiences. This text uses an engaging writing style and a consistent, organized template to present the concept of theory and help students become insightful, critical thinkers. The Connect course for this offering includes SmartBook, an adaptive reading and study experience which guides students to master, recall, and apply key concepts while providing automatically-graded assessments.